Cellular distribution and function of ion channels involved in transport processes in rat tracheal epithelium. Issue 12 (22nd June 2017) - Hahn, Anne; Faulhaber, Johannes; Srisawang, Lalita; Stortz, Andreas; Salomon, Johanna J; Mall, Marcus A; Frings, Stephan; Möhrlen, Frank
Abstract: Transport of water and electrolytes in airway epithelia involves chloride‐selective ion channels, which are controlled either by cytosolic Ca 2+ or by cAMP. The contributions of the two pathways to chloride transport differ among vertebrate species. Because rats are becoming more important as animal model for cystic fibrosis, we have examined how Ca 2+ ‐ dependent and cAMP‐ dependent Cl − secretion is organized in the rat tracheal epithelium. We examined the expression of the Ca 2+ ‐gated Cl − channel anoctamin 1 (ANO1), the cystic fibrosis transmembrane conductance regulator (CFTR) Cl − channel, the epithelial Na + channel ENaC, and the water channel aquaporin 5 (AQP5) in rat tracheal epithelium. The contribution of ANO1 channels to nucleotide‐stimulated Cl − secretion was determined using the channel blocker Ani9 in short‐circuit current recordings obtained from primary cultures of rat tracheal epithelial cells in Ussing chambers. We found that ANO1, CFTR and AQP5 proteins were expressed in nonciliated cells of the tracheal epithelium, whereas ENaC was expressed in ciliated cells. Among nonciliated cells, ANO1 occurred together with CFTR and Muc5b and, in addition, in a different cell type without CFTR and Muc5b. Bioelectrical studies with the ANO1‐blocker Ani9 indicated that ANO1 mediated the secretory response to the nucleotide uridine‐5′‐triphosphate. Our data demonstrate that, in rat tracheal epithelium, Cl − secretion and Na + absorption are routed through different cell types, and that ANO1 channels form the molecular basis of Ca 2+ ‐dependent Cl − secretion in this tissue. These characteristic features of Cl − ‐dependent secretion reveal similarities and distinct differences to secretory processes in human airways. Abstract : This paper demonstrates that ion channels involved in secretory activity show a different expression pattern in rat tracheal epithelium compared to the human trachea. Channels involved in secretion, CFTR, ANO1, and AQP5 reside in nonciliated cells, while ENaC is expressed in ciliated cells. Consequences of this expression pattern concerning regulatory processes of secretory activity are discussed.